Primerljivost delovnopravnega varstva v različnih oblikah zaposlitve - Kresal, Barbara (Delavci in delodajalci, 2012)
The paper deals with the problem of segmentation and dualism on the labour market, which causes the inequalities as regards the level of labour law protection for workers within different forms of employment. The non-standard, flexible, precarious employment puts employees in a more precarious situation, with less favourable labour and social conditions. The recent financial and economic crises have additionally contributed to the worsening of this problem. The paper offers a critical analysis of a concept of the co-called 'single' open-ended contract of employment (unified contract). Suggestions for the improvement of the existing legal regulation as regards different forms of employment are given, as well as suggestions for the improvement of its interpretation and implementation in practice.
Keywords: delovno pravo; fleksibilnost; pogodbe o zaposlitvi; pravno varstvo; trg dela; zaposlitev